Short-term investments and indices of risk - Yuval Heller; Amnon Schreiber (Theoretical Economics, 2020)
We study various decision problems regarding short-term investments in risky assets whose returns evolve continuously in time. We show that in each problem, all risk-averse decision makers have the same (problem-dependent) ranking over short-term risky assets. Moreover, in each problem, the ranking is represented by the same risk index as in the case of CARA utility agents and normally distributed risky assets.
Keywords: D81; G32; 330; Indices of riskiness; risk aversion; local risk; Wiener process